Pollution Monitoring Using Mytilus galloprovincialis and Fishes: A Case Study on the Southern Black Sea Shelf - Balkis, N.; Aksu, A.; Hiçsönmez, H. (Asian Journal of Chemistry, 2012)
In this study, the heavy metal bioaccumulations in mussels (Mytilus galloprovincialis) and fishes (Merlangius merlangus euxinus) have been studied along the Southern Black Sea Shelf. Generally, Pb and Cd contents were higher than the critical limits set by the Turkish Ministry of Environment for Aquatic Products (1 μg g-1 wet wt. and 0.1 μg g-1 wet wt., respectively) and European countries (2.0 μg g-1, UNEP, 1985). They showed increases towards the eastern end of the shelf. As contents were observed higher than the critical limits set by the Turkish Ministry of Environment for Aquatic Products (1.0 μg g-1 wet wt.) at stations Terkos, Samsun and Ordu in 2009. In contrast, Hg levels were also higher than the critical limits set by the Turkish Ministry of Environment for Aquatic Products (0.5 μg g-1 wet wt.) in 2005 and the highest Hg concentrations were found in the west and middle of the shelf.